Mate preferences in high and low social status groups - Tadinac, Meri; Hromatko, Ivana (2004)
The aim of this internet-based study was to test the hypothesis that not only sex, but also the social status, influences the importance and desirability of certain characteristics of a potential mate. Two extreme groups of heterosexual participants were selected from a larger sample (N=2675): "high-status group" - subjects who reported having high-income and high education and who rated themselves as above average looking (N=91) vs. "low-status group" - those who reported having low income and low education and who rated themselves as average or below average looking (N=82). Participants rated the importance and desirability of 18 characteristics (drawn from the Buss et al., 1990 study) of a potential mate on a four-point scale. MANOVA showed statistically significant main effects of sex and social status, as well as their interaction for some of the rated characteristics. Results are discussed in terms of mate-selection theories.
Projekt MZOS
ENG